The politicization of transatlantic trade in Europe: Explaining inconsistent preferences regarding free trade and the TTIP - Aleksandra Sojka; Jorge Diaz-Lanchas; Federico Steinberg (European Commission, Joint Research Centre (JRC), 2019)
The Transatlantic Trade and Investment Partnership (TTIP) generated an unprecedented contestation across Europe. In this paper, we focus on the sources of such backlash and analyze opinions on free trade and the specific agreement. Not accounting for the fact that these preferences are correlated could lead to biased conclusions about their determinants. To remediate this, we construct a set of bivariate probit models and calculate joint probabilities for the different types of preference configurations. We validate that support for free trade and support for the TTIP have similar, but not identical foundations. Inconsistent preferences are rooted in individual values, EU attitudes, and political cues, as well as treaty partner heuristics. Our innovative empirical approach offers an improved understanding of trade attitudes within EU's multilevel context.
Keywords: F60; F68; 330; trade liberalization; free trade; public opinion; trade agreements; TTIP